2020
DOI: 10.1136/bmjdrc-2020-001863
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic hematuria is a risk factor for end-stage kidney disease in patients with biopsy-proven diabetic nephropathy

Abstract: IntroductionThere are fewer reports about whether the presence of hematuria affects the progression of chronic kidney disease in patients with diabetic nephropathy. We analyzed whether microscopic hematuria in diabetic nephropathy is a risk factor for end-stage kidney disease (ESKD).Research design and methodsThe present study was a retrospective cohort study of patients with biopsy-proven diabetic nephropathy. We recruited 397 patients with diabetic nephropathy, which was confirmed by renal biopsy between Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Also, a recent report of biopsy-proven diabetic nephropathy showed that patients with advanced diabetic nephropathy were accompanied by a high prevalence of hematuria [27]. Another study confirmed that patients with biopsy-proven diabetic nephropathy and hematuria had more advanced pathological findings than those without hematuria, and the presence of hematuria is a significant risk factor for ESKD in patients with diabetic nephropathy [28]. Despite the above mentioned controversies, hematuria was an important criterion for kidney biopsy in our study population.…”
Section: Discussionsupporting
confidence: 57%
“…Also, a recent report of biopsy-proven diabetic nephropathy showed that patients with advanced diabetic nephropathy were accompanied by a high prevalence of hematuria [27]. Another study confirmed that patients with biopsy-proven diabetic nephropathy and hematuria had more advanced pathological findings than those without hematuria, and the presence of hematuria is a significant risk factor for ESKD in patients with diabetic nephropathy [28]. Despite the above mentioned controversies, hematuria was an important criterion for kidney biopsy in our study population.…”
Section: Discussionsupporting
confidence: 57%
“…10 Several studies also reported that microscopic hematuria is a risk factor of end-stage kidney disease in patients with diabetic nephropathy. 18,19 However, these studies were conducted in populations with existing renal conditions and did not directly assess the role of hematuria as early signs of asymptomatic chronic kidney disease. Another community-based cohort study of 8,719 Korean participants showed that microscopic hematuria was associated with increased risk of incident CKD in the general population setting.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 There were few studies reporting that microscopic hematuria was a risk factor for end-stage kidney disease in diabetic nephropathy, and was associated with worse renal outcomes more strongly in men. 18,19 However, no previous studies have evaluated sex-related differences in the association between microscopic hematuria and CKD. .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, persistent hematuria was reported to be associated with an increased risk of ESRD in IgA nephropathy [ 13 ]. The degree of proteinuria definitely correlates with the risk of diabetic kidney; however, microscopic hematuria is also a dependent risk factor for ESRD in diabetic nephropathy [ 14 ]. These suggest that the presence of nondiabetic renal disease in patients with diabetic CKD carries a relatively high risk of renal progression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%